Experimental Investigation and Computer-Generated Simulation of Reinforced Double-Tee Girders with a Wall of Oriented Standard Board - Dmytrenko, Andrii; Dmytrenko, Tetiana; Derkach, Tetyana; Klochko, Lina (International Journal of Engineering and Technology, 2018)
The problem of sustaining capacity increasing of wooden structures and elements which operate in lateral deflection is always in the researchers’ focus of interest, this caused the composite wooden structures creation. One of the ways to improve and increase wooden structures’ technical-and-economical efficiency is bar reinforcement, which allows to increase structures’ resistibility and rigidness, safety and lasting quality.The results of experimental investigation of reinforced wooden I-beam with a web of oriented standard wall operation are given in this research paper. The peculiarity of this I-beam is boom fiber-glass reinforcement. The experiment task is to determine the operation characteristics and stress strain behavior of composite beam elements.In the article, the authors provided a description of the proposed and patented design constructive solution of reinforced double-tee girders with a wall of oriented standard board, which was made of two boards with 38 x 65 mm cross-section and 10 mm x 200 mm wall of oriented standard board (oriented standard board - OSB), which connected with epoxy adhesive, the height of beam is 250 mm.The experiment results analysis of suggested I-beams with fiber-glass reinforcement was carried out, the operation under the load peculiarities and fracture mode was revealed.